2020
DOI: 10.1002/anie.202008372
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Stability and Reactivity of Aryl Germanes Enables Rapid and Selective (Multi)Halogenations

Abstract: While halogenation is of key importance in synthesis and radioimaging,t he currently available repertoire is largely designed to introduce as ingle halogen per molecule.T his report makes the selective introduction of several different halogens accessible.S howcased here is the privileged stability of nontoxicaryl germanes under harsh fluorination conditions (that allows elective fluorination in their presence), while displaying superior reactivity and functional-group tolerance in electrophilic iodinations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 95 publications
(4 reference statements)
0
33
0
Order By: Relevance
“…For aryl N -CF 3 carbamoyl fluorides that bear strongly electron withdrawing substituents (e.g., sulfone or bearing multiple halogens), we encountered competing decarbonylation. However, masking groups, such as GeEt 3 ( 2 ), could be tolerated in the cross-coupling which allows the possibility of potentially introducing such functionality in follow-up transformations. , The method also proved effective at the 1 mmol scale and with lower catalyst loading (2.5 mol %) ( 1 and 11 , Figure ).…”
mentioning
confidence: 99%
“…For aryl N -CF 3 carbamoyl fluorides that bear strongly electron withdrawing substituents (e.g., sulfone or bearing multiple halogens), we encountered competing decarbonylation. However, masking groups, such as GeEt 3 ( 2 ), could be tolerated in the cross-coupling which allows the possibility of potentially introducing such functionality in follow-up transformations. , The method also proved effective at the 1 mmol scale and with lower catalyst loading (2.5 mol %) ( 1 and 11 , Figure ).…”
mentioning
confidence: 99%
“…7 They are nontoxic 8 andin contrast to boronic acidsproved to be highly robust to acids and bases as the corresponding pentafluoroaryl or 2pyridyl motifs, for example. 9 Moreover, efficient coupling protocols could recently be devised that enable the orthogonal functionalization of aryl germanes in the presence of typical Pd-based cross-coupling functionalities (such BPin, halogens), 10,11 which adds a dimension of modularity in chemoselective coupling reactions.…”
mentioning
confidence: 99%
“…7 Extending these protocols to the herein made heterocyclic motifs, we observed that these are similarly effective coupling partners under our Pd-nanoparticle conditions. 9 Efficient coupling of 1-methyl-2-(triethylgermyl)indole with 4-fluoroiodobenzene was achieved using 2.5 mol % of Pd 2 dba 3 and 1.5 equiv of AgBF 4 in DMF at 80 °C (to give 25 in 86% yield, Scheme 2). This type of coupling with heteroaryl boronic acid has been challenging due to their propensity to undergo protodeboronation.…”
mentioning
confidence: 99%
“…The synthetic methods for organogermanium compounds have been less studied than those of other group 14 homologues, such as organosilicon and organotin compounds, although the organo­germanium compounds are potentially useful synthetic reagents and organic molecular materials . One of the promising germanium-based organic molecular materials is a germole, germacyclo­pentadiene.…”
mentioning
confidence: 99%